Successful educational actions as the basis of evidence-based educational policy - Flecha García, Ramón; Molina Roldán, Silvia (Avances en Supervisión Educativa, 2015)
In this paper we address the need to base education policy on scientific evidence. For this purpose, we base our argument on contributions from two research projects. On the one hand, the INCLUD-ED project has provided the identification of successful educational actions, whose components, universal and transferable, are an added value for policy development. On the other hand, the IMPACT-EV project aims to help improve the social impact of research in social sciences and humanities. Understanding social impact as the improvements achieved in relation to social goals such as education, employment and poverty, we argue that policies developed based on scientific evidence have greater potential to achieve social impact. This approach of policy development responds to citizens’ demands to get not only more stable policies but also more scientific, which ensure greater equality of educational outcomes.
Keywords: educational policy; democratization of education; educational reform